The Influence of Earning Per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE) on Stock Prices of Banking Companies Listed on the Indonesia Stock Exchange for the Period 2020–2024 - Dhelliyanti, Dhelliyanti; Ambarwati, Ambarwati (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to examine the impact of Earnings Per Share (EPS), Return on Assets (ROA), and Return on Equity (ROE) on stock prices of banking companies in the digital era listed on the Indonesia Stock Exchange during the 2020–2024 period. This study employs a quantitative approach using multiple linear regression to analyze the financial data of banking companies listed on the Indonesia Stock Exchange.The results indicate that individually, the Earnings Per Share (EPS) and Return On Equity (ROE) variables each have a significant impact on stock prices, while Return On Assets (ROA) has a positive but insignificant impact. On the other hand, all three variables collectively have a significant impact on stock prices. The Adjusted R-Square value of 0.482 indicates that Earnings Per Share (EPS), Return On Assets (ROA), and Return On Equity (ROE) account for approximately 48.2% of the variation in stock prices, while the remainder is influenced by other factors not covered in this study.Thus, it can be concluded that financial performance, as measured by profitability indicators such as Earnings Per Share (EPS) and Return On Equity (ROE), remains a crucial benchmark for investors when evaluating banking stocks, particularly in the context of increasing digitalization in the financial sector. This study is expected to serve as a reference for bank management, investors, and other researchers in undestanding